2022
DOI: 10.1063/5.0070167
|View full text |Cite
|
Sign up to set email alerts
|

An in-plane omnidirectional piezoelectric wind energy harvester based on vortex-induced vibration

Abstract: Variations in the wind direction over time mean that it is essential to improve the directional adaptability of wind energy harvesters (WEHs) based on wind-induced vibration (WIV) to expand their application potential. Several multi-directional WIV WEHs have been reported in the literature but most of them are not omnidirectional. In particular, no mathematical model has been proposed for omnidirectional WIV WEHs to date. In this Letter, an in-plane omnidirectional piezoelectric WEH with a cylindrical shell, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The experimental result demonstrated the capability of collecting wind energy in two orthogonal directions with the U-shaped supporter. Li et al [20] successively developed a VIV piezoelectric wind energy harvester with a cylinder shell, which could adapt to omnidirectional incident wind due to its geometric characteristic. Gong et al [21] proposed a direction-adaptive VIV-based energy harvester with a guide wing to capture flow energy.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental result demonstrated the capability of collecting wind energy in two orthogonal directions with the U-shaped supporter. Li et al [20] successively developed a VIV piezoelectric wind energy harvester with a cylinder shell, which could adapt to omnidirectional incident wind due to its geometric characteristic. Gong et al [21] proposed a direction-adaptive VIV-based energy harvester with a guide wing to capture flow energy.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [47] showed in their experiments that the output performance of the cross-double-beam configuration outperformed the single-beam configuration visibly. Afterwards, Li et al [48] reported a unique energy harvester made up of three semicircular piezoelectric beams and a hollow cylinder. Both experimental and theoretical findings demonstrated that the designed harvester was capable of harnessing wind energy from any incoming flow direction in the horizontal plane.…”
Section: Introductionmentioning
confidence: 99%
“…However, the VIV-based energy harvester (VIVEH) generally works well as the shedding frequency coincides with the natural frequency of structure. To extend the synchronization range and improve the VIV energy harvesting performance, plenty of studies including the optimization of bluff body [12][13][14][15][16][17][18][19][20], the introduction of non-linearity [21][22][23][24][25][26][27] and the interference effects of bluff bodies [28,29] have been conducted. Dai et al [12] investigated the orientation of bluff body so as to get the best performance of VIV energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [12] investigated the orientation of bluff body so as to get the best performance of VIV energy harvesting. Li et al [13] proposed an in-plane omnidirectional piezoelectric VIV-based wind energy harvester with a cylindrical shell and curved beams to expand the working wind direction range. Jin et al [14] investigated the use of bionicshaped attachments for improving the harvested energy.…”
Section: Introductionmentioning
confidence: 99%